Isu LGBT Dalam Bingkai Media Online (Analisis Framing Robert Entman Pada Pemberitaan RKUHP LGBT Pada Tempo.co Dan BBBCIndonesia.com) - Rety Palupi; Muhammad Habibur Rahmansyah; Ghifary Muhammad Arasta; Gema Irhamdhika (Jurnal Media Penyiaran, 2022)
The government has planned and submitted the RKUHP to the DPR, but the RKUHP has sparked a polemic. According to an article published by the online media Kumparan. The meeting between Commission III of the DPR RI and the Government represented by the Ministry of Law and Human Rights on Wednesday, May 25, 2022, discussed the Draft Criminal Code (RKUHP) whose ratification has been delayed since September 2019. What has become a polemic again is that there is an article that discusses the criminalization of Lesbians. , Gay, Bisexual, and Transgender (LGBT). Based on the background of the problem, the researcher conducted an analysis in the online media Tempo.co and BBCIndonesia.com.The purpose of this study was to find out how the online media Tempo.co and BBCIndonesia in framing a news report on the issue of the LGBT RKUHP. The research approach uses qualitative research methods with framing analysis methods. The researcher uses an analytical method with the Robert N. Entman model, with four stages in framing a news, namely: Define Problems (defining the problem), Diagnoses Causes (estimating the problem), Make Moral Judgment (making moral decisions), and Treatment Recommendation (emphasizing the solution).The results of the research show that Tempo.co is more neutral in responding to this news issue by presenting sources who explain in detail the articles in question, while BBCIndonesia.com shows a contra stance against the RKHUP on the criminal offense of obscenity by presenting sources who oppose and feel criminalized by the existence of the article.